Atmosphere-Dependent Photoconductivity of ZnO in the Urbach Tail. (21st October 2018) - Scolfaro, D.; Onofre, Y. J.; Teodoro, M. D.; de Godoy, M. P. F.
Abstract : Photoconductivity is a fundamental and highly applicable phenomenon for semiconductor oxide-based devices, and the presence of defects plays a significant role in this mechanism. Here, we present an investigation based on different atmospheres and light excitation (above and below bandgap) dependences of zinc oxide thin film grown by spray-pyrolysis. As-grown ZnO presents a representative Urbach tail associated to the presence of localized levels in the bandgap. Photoconductivity response and decay times are investigated for air and inert atmospheres as well as under vacuum conditions with significant features due to light excitation conditions. The observed characteristics are explained based on oxygen photodesorption when excitation is above bandgap while this process is suppressed when excitation is below bandgap.